Comprehensive Proteomic Characterization Reveals Subclass-Specific Molecular Aberrations within Triple-negative Breast Cancer - Kosok, Max; Alli-Shaik, Asfa; Bay, Boon Huat; Gunaratne, Jayantha (iScience, 2020)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer lacking targeted therapies. This is attributed to its high heterogeneity that complicates elucidation of its molecular aberrations. Here, we report identification of specific proteome expression profiles pertaining to two TNBC subclasses, basal A and basal B, through in-depth proteomics analysis of breast cancer cells. We observed that kinases and proteases displayed unique expression patterns within the subclasses. Systematic analyses of protein-protein interaction and co-regulation networks of these kinases and proteases unraveled dysregulated pathways and plausible targets for each TNBC subclass. Among these, we identified kinases AXL, PEAK1, and TGFBR2 and proteases FAP, UCHL1, and MMP2/14 as specific targets for basal B subclass, which represents the more aggressive TNBC cell lines. Our study highlights intricate mechanisms and distinct targets within TNBC and emphasizes that these have to be exploited in a subclass-specific manner rather than a one-for-all TNBC therapy. [Display omitted] •Proteome profiling reveals functionally distinct subclasses within TNBC•Kinases and proteases underlie unique functional signatures among the subclasses•Kinase-protease-centric networks highlight subclass-specific molecular rewiring•Protein association dysregulations reveal TNBC subclass-specific protein targets Biological Sciences; Cancer Systems Biology; Cancer; Proteomics